Exploration of key success factors that influence business performance: The experiences of women micro-entrepreneurs from Mazovia Voivodeship of Poland - Dariusz Leszczyński (International Journal of Management and Economics, 2016)
Women-owned businesses are one of the fastest growing categories of firms in the world, but they are greatly understudied in countries from the Central and Eastern Europe (CEE) [Zapalska et al., 2005]. The purpose of this paper is to examine the relationship between business success predictors and the performance of female-owned micro-enterprises from the Mazovia Voivodeship in Poland during the period 2011-2013, using an Internet-based survey questionnaire. The data were collected by the CAWI (computer assisted web interview) and CATI (computer assisted telephone interview) methods. Exploratory factor analysis, correlation coefficients analysis and multivariate regression models were deployed to investigate the empirical data. This study contributes to the limited body of literature on factors that positively affect the business performance of female entrepreneurial undertakings, using the context of the Polish experiences. Drawing on Gartner's [1985] typology and "the resource-based view of the firm" theory, a theoretical research model was developed and verified empirically using three multivariate regression models. "Model A" displayed the highest explanatory power of the predicted dependent variable "Composite business performance" (R2 = 42,3). Our findings suggest that the most successful female business owners in the region were ideally 30-39 years old; completed a university education; had at least three years of business experience; displayed above average entrepreneurial orientation; and adopted a business strategy to deal with competitors. Moreover, the better performing women-owned micro-enterprises hired qualified and experienced employees ("hman capital"); offered products or services to domestic and international customers; were able to attract business sector clients; and had sufficient resources ("financial capital"). It is recommended that this research be replicated in other countries from the CEE region (e.g. Czech Republic) for comparative purposes.
Keywords: C21; L10; M19; M21; M31; 650; business performance; micro-enterprise; Poland; success factors; woman micro-entrepreneur